'Who were you crying for?': Empathy, fantasy and the framing of the perpetrator in Nina Bunjevac's Bezimena. Issue 2 (1st November 2020) - Manea, Dragoş; Precup, Mihaela
Serbian-Canadian cartoonist Nina Bunjevac's third book, Bezimena (2019), embeds child sexual abuse and murder in an improbable geography where myth and fairy tale work together to create an otherworldly atmosphere, by turns mesmerizing and horrifying. Bunjevac's previous work (Heartless [2012] and Fatherland [2014]) testifies to her continued commitment to exploring issues that are relevant to the feminist project, such as domestic violence, abortion, sexual assault and discrimination against female immigrant workers. In this article, we are particularly interested in exploring the manner in which Bezimena frames the figure of the perpetrator, as the context of the final question of the book ‐ 'who were you crying for?' ‐ repositions the entire ethical premise of the narrative by suggesting that responsibility for perpetration may lie both within and without the body and consciousness of the perpetrator himself. In conversation with scholars who attempt to expand the narrow category of 'perpetrator', such as Michael Rothberg or Scott Strauss, we explore how graphic narratives can contribute to a more nuanced understanding of perpetration, particularly in the case of sexual assault, and analyse Bezimena's innovative approach to the representation of perpetration, as the book's depiction of perpetrators and accomplices is mixed with elements of fantasy and mythology.